The effect of anxiety on performance of University Kebangsaan Malaysia athletes - Sharlyn Samadin @ Lamdin,; Mohamad Nizam Nazarudin,; Zakiah Noordin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study was conducted to identify the perception of Silat athletes of Universiti Kebangsaan Malaysia on the effects of anxiety on sports performance (physiological, psychological, and behavioural perspective). A total of 30 Silat athletes consisting of 30 male athletes and 30 female athletes were randomly selected to answer an Anxiety Effect Performance Perception questionnaire (AEPPQ) from Muhammad et al (2107). Data were collected during the training session and analysed using descriptive statistics. The result demonstrates that anxiety has a high level of impact on both physiological and psychological performance. With the exception of the statement that anxiety impairs relationships with friends, family, and teammates, and anxiety makes someone furious to a modest extent. The impacts of anxiety on behavioural performance are at a high degree. Both positive and negative have impacts of anxiety on Silat Athletes' performance. Additionally, several techniques including deep breathing, mental practise, and encouraging self-talk were proposed as ways to help Silat athletes deal with nervousness. It is advised that future studies include a bigger sample of Silat athletes from all Malaysian Higher Education Institute